THE IMPACT OF PRICE AND CORPORATE VALUES ON THE CUSTOMER LOYALTY: MEDIATING ROLE OF CUSTOMER SATISFACTION - Hamid, Junainah Abd; kKhatibi, Ali; Tham, Jacqueline (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the current work is to inspect the price and corporate value’s impact on the customer loyalty in the Malaysian telecommunication companies. Another purpose of the existing study is to examine the mediating role of customer satisfaction among the nexus of price and corporate value and customer loyalty. Over the past decade companies have pointed to the ability to manage their telecommunication services supply, particularly given the expanding and changing nature of the telecommunication services market. Detailed case research into major telecommunication arrangements must be found that investigate the marketing relationship dimension that exists between the customers and telecommunication service providers as it is critical and complex to understand.